Pengaruh Pengalaman dan Keterampilan Kerja Terhadap Pengembangan Karir pada Dinas Pendidikan dan Kebudayaan Provinsi Gorontalo - Arlan Ida; Rizan Machmud; Rezkiawan Tantawi (Economic Reviews Journal, 2024)
Based on the results of the analysis, the results of this study are either partially or simultaneously the variables of experience and work skills are proven to have an influence on career development at the Office of Education and Culture of Gorontalo Province. Partially, work experience has a positive and significant effect on career development, this is based on the results of the Work Experience Variable t test = t count 2.835> t table 1.976 and a significance value of 0.005 < 0.05. This shows that if employees have good work experience, employees will have a good opportunity to develop careers. The work skills variable has a positive and significant effect on career development. Based on the results of the X2 t test = t count 2.642> t table 1.976 and a significance value of 0.009 <0.05. Work skills have a positive and significant effect on career development. So that if work skills increase, career development opportunities will increase.